RNO-G detection perspectives of binary neutron star mergers - Cataldo, Maddalena (Proceedings of the International Astronomical Union, 2020)
The Radio Neutrino Observatory Greenland (RNO-G) is currently being deployed and it is currently gathering data. As a precursor and complementary detector to the future radio array of IceCube-Gen2 in Antarctica, it will explore mainly the Northern sky via in-ice radio detection technique. The total array configuration includes 35 radio stations and will be fully completed within three years from now. The antennas will register the radio signals produced by the Askaryan effect in cascades generated in ice by neutrinos. RNO-G's scientific purpose is to detect UHE neutrinos at energies above 10 PeV. Due to the attenuation length of radio waves in ice (order of 1 km) the radio detection allows to address neutrino energies above several PeV. The detector will reach unprecedented sensitivity in the scale from tens of PeV up to EeV. Models predict GRBs induced by binary neutron star mergers as likely transient sources of such highly energetic neutrinos. The current study of NS-NS mergers will therefore possibly be complemented by future RNO-G detections through multimessenger temporal and spatial coincidence, including an alert system. In this presentation, we will describe the instrument capabilities and explore the possibility of detection of such sources with RNO-G.
CRIS-Team Scopus Importer:2024-12-16
Keywords: acceleration of particles; neutrinos; stars: neutron